The Ethics of Lives in Rusunawa in Islamic Perspective - Retnowati WD Tuti; Oneng Nurul Bariah; Mawar Mawar; Kurniasih Mufidayati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This paper describes the ethics of living in Rusunawa in Islamic Perspective. Rusunawa is a rented apartment tothe community. The writing of this paper is motivated by the findings of the lives of Muslims who live inrusunawa not in accordance with the values of Islamic law such as not keeping promises, not maintaining theenvironment, and others. Data collection was done by observation, interview, brainstorming, and literature study.Ethics of life in the Rusunawa Islamic perspective is to behave in accordance with the guidance of Islamic lawcontained in the Qur'an and sunnah of the Prophet. These ethics include: being honest, trustworthy, being frugal,keeping the environment clean, respecting each other, helping, and maintaining environmental security.  Keywords: rusunawa, ethics, islam, life